Measuring Functional Status in Huntington's Disease. Issue 3 (27th October 2020) - Gibson, Jessie S.; Ridner, Sheila H.; Dietrich, Mary S.; Sohn, Michael B.; Rhoten, Bethany A.; Claassen, Daniel O.
Abstract: Background: Neuropsychiatric and cognitive symptoms account for substantial morbidity in Huntington's disease (HD), but their impact on functional status may not be captured using the Total Functional Capacity (TFC) scale. The objective of this study was to assess the impact of motor, cognitive, and neuropsychiatric symptoms on functional status in persons with HD, comparing two instruments. Methods: Multiple regression analyses assessed the relationship between neuropsychiatric, cognitive, and motor symptoms and functional status as measured using TFC and Adult Functional Adaptive Behavior (AFAB) scales. Results: Greater burden of neuropsychiatric ( P = 0.017), cognitive ( P = 0.001), and motor ( P = 0.001) symptoms was associated with greater impairments to functional status as measured by the AFAB scale. Only motor symptoms were associated with TFC scores ( P = 0.002). The 3 symptom domains explained more of the variance in AFAB than TFC scores ( P = 0.016). Conclusions: TFC may have limited applicability, particularly in early‐stage HD patients, as a measure of functional status. The AFAB scale can be used in HD studies as a more holistic measure of functional status. © 2020 International Parkinson and Movement Disorder Society